PENGARUH PER CEIVED USEFULNESS TERHADAP KEPUTUSAN PEMBELIAN DI APLIKASI SHOPEE - Nursakinah Ritonga (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
This study aims to explain and analyze the effect of perceived usefulness on purchasing decisions on the Shopee application. The population of this research is Active Students of Business Administration Study Program, FISIP, UNIMAL, totaling 312 people. The number of samples in this study was taken using the Yamane formula with a standard error of 10% so that the number obtained was 76 people. The data analysis technique consists of several tests, namely the research instrument test which consists of validity and reliability testing and hypothesis testing using regression testing on the SPSS application. Based on the results of simple linear regression analysis, it is known that perceived usefulness has a positive effect on Purchase Decisions on the Shopee application among Business Administration Students, FISIP UNIMAL because the coefficient value obtained is positive, namely 0.576. Based on the results of the partial test or t test, the results show that perceived usefulness has a significant effect on purchasing decisions